Re-interpreting Culture as a Pedagogical Reference in Religious Education: A Metasynthesis in the Hermeneutic Cycle - Temporal, Wilson; Temporal, Wilson (International Journal of Arts, Sciences and Education, 2021)
Religious pluralism in the classroom brings with it multiculturalism that necessitates careful interpretation. Hence, this study aimed to reinterpret culture as a pedagogical reference in Religious Education. The study made use of both hermeneutic phenomenological research method and descriptive meta-synthesis. Results show four essential themes that emerged in the analysis, namely: the cultural context, dispositions in Religious Education, tenets of culture vis-à-vis typologies in Religious Education, and pedagogies towards integrated approach to Religious Education - interplay of faith and culture. Keywords: culture, catechesis, pedagogy, education, religious education, faith, meaning, values, hermeneutic, pluralism, phenomena